MIDGUT TREHALASE IN FIFTH INSTAR LARVA OF ANTHERAEA PROYLEIJ. (LEPIDOPTERA: SATURNIIDAE) - KUMBHAR, V.J.; GAIKWAD, S.M.; GAIKWAD, Y.B.; BHAWANE, G.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The effect of pH, temperature optima, time, Michaelis constant, thermolability and rate curve for trehalase in fifth instar larvae of Antheraea proylei were studied. The optimum pH and optimum temperature for midgut trehalase was 6.0 and 40°C, respectively and the Km value obtained was 2.11 x 10-3 M. The 50% inhibition at higher temperature 60°C was found to be 11 min. The specific activity was 0.9825 ug glucose/ ug protein/ h.